Mapping the margins : the family and social discipline in Canada, 1700-1975 - Gauvreau, Michael, 1956-; Christie, Nancy, 1958- (McGill-Queen's University Press, 2004)
Contributors include Denyse Baillargeon (Université de Montréal), Bettina Bradbury (York University), Josette Brun (Université Laval), Nancy Christie (Hamilton), Gwendolyn Davies (University of New Brunswick), Michael Gauvreau (McMaster University), Peter Gossage (Université de Sherbrooke), Ollivier Hubert (Université de Montréal), Jack Little (Simon Fraser University), James Moran (University of Prince Edward Island), Suzanne Morton (McGill University), Matt Savelli (McMaster University), Michele Stairs (York University), James Struthers (Trent University), and David Wright (McMaster University).